2015
DOI: 10.1155/2015/258161
|View full text |Cite
|
Sign up to set email alerts
|

The Motor Recovery Related with Brain Lesion in Patients with Intracranial Hemorrhage

Abstract: Although studies have demonstrated that several specific brain lesions are related to the severity of functional outcomes, the effects of specific brain lesions are not yet clear. This study investigated the effects of hemorrhagic stroke lesions on motor recovery. Eleven subjects with hemorrhagic stroke were assessed. Using the Fugl-Meyer Assessment and functional ambulation category, clinical motor and sensory impairments were tested four times in total: initially within 2 weeks and 1, 3, and 6 months after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 21 publications
2
34
0
2
Order By: Relevance
“…This study was an observational one for clinical recovery and outcome, we did not calculate the exact sample size. Sample sizes of previous studies vary 11–41 (Lee et al., ; Lee et al., ; Shelton & Reding, ). We decided the sample size was thirty subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was an observational one for clinical recovery and outcome, we did not calculate the exact sample size. Sample sizes of previous studies vary 11–41 (Lee et al., ; Lee et al., ; Shelton & Reding, ). We decided the sample size was thirty subjects.…”
Section: Methodsmentioning
confidence: 99%
“…All subjects received physical and occupational therapy on the basis of a neurodevelopmental treatment approach (physical therapy) and task‐orientated approach (occupational therapy). The rehabilitation program of all subjects had started within 1 month after onset (Lee et al., ). The treatment continued up to 6 months after onset, consisted of 1–2 hrs per day, 5 days a week, including each of physical and occupational therapy.…”
Section: Methodsmentioning
confidence: 99%
“…For precise localization of their brain lesions, high resolution 1.5T anatomical MRI scans with a 5-mm slice thickness were analyzed using MRIcron, SPM8, and Talairach Daemon software [8]. …”
Section: Methodsmentioning
confidence: 99%
“…This prolonged recovery is a witness to the beneicial outcome of rehabilitation during the subacute phase of recovery in stroke patients [25]. Neuronal plasticity is a subject of dedicated study today and is deined as the ability of the brain to recover functionally due to neuronal reorganization after a cerebral insult.…”
Section: Rehabilitation and Recoverymentioning
confidence: 99%
“…Impaired motor functions can be due to paralysis or paresis of the muscles (depending on the site of the lesion), which results from the damage to the brain parenchyma (motor cortex or descending/ascending pathways in the internal capsule and corona radiata), resulting in abnormal regulation of spinal motoneurons, alterations in postural and stretch relexes and loss of voluntary movements [18,[53][54][55][56]. If the lesions involve the internal capsule, thalamus, periventricular white mater, and/or premotor cortex, the recovery of the upper limb motor functions is poorer [25,57]. Regarding the functions in the lower limbs, in a study, it was shown that approximately 51% of subjects were without walking function at the time of admission to the rehabilitation unit and 12% of the subjects needed assistance during ambulation [58].…”
Section: Impaired Motor Functionmentioning
confidence: 99%